Adaptive control of uncertain systems with input saturation - Mi, Muxin (2016)
This report discusses a proposed adaptive control scheme that regulates uncertain systems with input saturation nonlinearities. It presents and examines the fundamental theories in the field of recursive backstepping control, including integrator backstepping control, adaptive control, and adaptive control with tuning functions which lay the foundations for the main topic of discussion of this report. It continues with discussions on the research results of the proposed adaptive control scheme, covering the theoretical backgrounds of the proposed control scheme, as well as implementation of the control scheme through MATLAB Simulink simulations. This report also studies the effects of key system parameters and proposes recommendations for system tuning.